Dampak Pandemi COVID-19 terhadap Kinerja Perusahaan di Moderasi Pendapatan - Maria Jessica Junaidi, Susanto Salim (Jurnal Ekonomi, 2021)
This study aims to determine the effect of the COVID-19 pandemic on company performance moderated by firm’s revenue and the difference between company's performance before and during the COVID-19 pandemic. The population of this study are consumer goods companies listed on the IDX in 2019-2020 and sample of 56 companies are obtained from the purposive sampling method. The year 2019 represents the period before the pandemic and the year 2020 represents the period of the pandemic. The company's performance is indicated by the profitability ratio in the form of Return On Assets. This study uses moderated regression analysis and the Wilcoxon sign rank test. The results of this study indicate that there is a negative and significant difference between the company's performance before and during the pandemic. The results of this study also show that the firm’s revenue isn’t moderating the effect of the COVID-19 pandemic on company performance.